Den transatlantiske ledestjerne. Sikkerhedspolitiske tendenser og realiteter i Danmark 2019-2024 - Schmidt, Jakob Linnet (Historisk Tidsskrift, 2024)
The Transatlantic Lodestar: Security Policy Trends and Realities in Denmark, 2019–2024 Denmark has recently witnessed seismic changes in its security and defence policy. This article argues that a desire to establish the closest possible bond with the US and prove a good ally is guiding Denmark’s foreign policy. This has led to a break with established policies, including not allowing the stationing of allied forces in peacetime and limiting defence expenditure to a minimum. A defence cooperation agreement has thus been concluded with the US allowing American military personnel and material in Denmark, and, for the first time in Danish history, defence expenditure meets NATO’s guidelines. These changes occurred when it was increasingly clear that the post-Cold War period, characterized by a relatively peaceful relationship between the West and Russia, was definitively over, and the US security guarantee seemed more fragile than ever. The risk of abandonment outweighed the dangers of entrapment. The Danish government thus strengthened the priority of maintaining the closest possible ties with the US. This desire was so pronounced that in cases of disagreements between Europe and the US, Denmark has sided with the latter. This has led to a weakening of the European dimension, although hardly due to aversion to European cooperation, but rather to the desire for transatlantic cooperation. The 2022 referendum that led Denmark to rejoin the defence cooperation coordinated by the EU(abandoned by Denmark 1993) was not initiated by the government. Nevertheless, it points towards a more active Danish participation in European defence cooperation as a supplement to the dominating transatlantic orientation in Danish security and defence policy.